THE FORMING OF COMMUNICATIVE COMPETENCE OF FUTURE TEACHER OF ENGLISH - Bazyliak, Natalia O. (Educological discourse, 2014)
The article presents effective pedagogic technology of forming communicative competence of the future teacher of English as foreign language. The sequential theoretical analysis and practical development of this model is provided; the comparison, typology to language practice is presented. The basic preconditions and mechanisms of speech practice strategies in the context of modern pedagogic investigations is done.